Improvement in left ventricular dysfunction after surgical correction of mitral regurgitation - Rocha,Antônio Sérgio Cordeiro da (2003)
OBJECTIVE: To evaluate whether left ventricular end-systolic (ESD) diameters £ 51mm in patients (pt) with severe chronic mitral regurgitation (MR) are predictors of a poor prognosis after mitral valve surgery (MVS). METHODS: Eleven pt (aged 36±13 years) were studied in the preoperative period (pre), median of 36 days; in the early postoperative period (post1), median of 9 days; and in the late postoperative period (post2), mean of 38.5±37.6 months. Clinical and echocardiographic data were gathered from each pt with MR and systolic diameter ³51mm (mean = 57±4mm) to evaluate the result of MVS. Ten patients were in NYHA Class III/IV. RESULTS: All but 2 pt improved in functional class. Two pt died from heart failure and infectious endocarditis 14 and 11 months, respectively, after valve replacement. According to ejection fraction (EF) in post2, we identified 2 groups: group 1 (n=6), whose EF decreased in post1, but increased in post2 (p=0.01) and group 2 (n=5), whose EF decreased progressively from post1 to post2 (p=0.10). All pt with symptoms lasting £ 48 months had improvement in EF in post2 (p=0.01). CONCLUSION: ESD ³51mm are not always associated with a poor prognosis after MVS in patients with MR. Symptoms lasting up to 48 months are associated with improvement in left ventricular function.